Respon Hasil Tanaman Kubis Bunga (Brassica oleracea Var. Botrytis L.) Kultivar PM 126 F1 Terhadap Pemberian Kombinasi Pupuk NPK dan Pupuk Organik Cair dari Limbah Organik - Nisa, Nida Aola; Rahmi, Hayatul; Rahayu, Yayu Sri (JURNAL AGROPLASMA, 2023)
The constraints to cauliflower production until now are increasingly limited land and the continuous use of chemical fertilizers which can reduce soil quality. This study aims to obtain a combination of NPK fertilizer and Liquid Organic Fertilizer (POC) organic waste which has the best effect on the growth and yield of cauliflower PM 126 F1 cultivation. The research method used was the single factor randomized block design (RBD) experimental method. The factors tested were a combination of NPK fertilizer and POC organic waste with 8 treatments and 4 replications, namely A (800 kg/ha NPK), B (200 ml/L), C (640 kg/ha NPK + 100 ml/L), D (640 kg/ha NPK + 200 ml/L), E (640 kg/ha NPK + 300 ml/L), F (480 kg/ha NPK + 100 ml/L), G (480 kg/ha NPK + 200 ml/L), H (480 kg/ha NPK + 300 ml/L). The results of analysis of variance and DMRT at 5% level explained that the combination of NPK fertilizer and POC organic waste significantly affected crop heighand crop weight per plant. Treatment C gave the best results for crop height 7.60 cm; crop diameter 11.40 cm; and crop weight per plant 114.50 grams. Keywords: Cauli flower, NPK Fertilizer, Liquid Organic Fertilizer, Organic Waste